Re‐elevation of serum amlodipine level after lipid emulsion therapy in an overdose case. (22nd August 2019) - Ando, Motozumi; Nakasako, Shinji; Ariyoshi, Koichi; Yamaguchi, Marie; Sakizono, Kenji; Minowa, Kazushi; Fukushima, Shoji; Sugioka, Nobuyuki; Hashida, Tohru
Abstract: What is known and objective: Amlodipine overdose is common; however, the dose and timing of intravenous lipid emulsion (ILE) therapy as a management strategy remain debatable. Case description: A 73‐year‐old man received a single bolus (1.5 mL/kg) of ILE therapy following massive ingestion of multiple drugs, including amlodipine. After approximately 20 hours of ILE therapy, the serum amlodipine level that had decreased from 90.2 to 49.9 ng/mL increased to 70.8 ng/mL. What is new and conclusion: A single bolus (1.5 mL/kg) of ILE therapy is probably insufficient to completely capture and partition serum amlodipine following amlodipine overdose. Abstract : Re‐elevation of serum amlodipine level was observed after single bolus of ILE therapy. It is deemed desirable to perform ILE infusion following its bolus in a case of amlodipine overdose.